Advanced security and privacy for RFID technologies - Miri, Ali.; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2013)
"This book addresses security risks involved with RFID technologies, and gives insight on some possible solutions and preventions in dealing with these developing technologies"--Provided by publisher.
Security terminology / Ming Li -- RFID standards / Ilker Onat, Ali Miri -- RFID wireless link threats / Ilker Onat, Ali Miri -- Hardware attacks / Fanyu Kong, Ming Li -- Computer system attacks / Zhang Ning -- An overview of cryptography / Ehsan Vahedi, Vincent W.S. Wong, Ian F. Blake -- Identification and authentication for RFID systems / Behzad Malek -- Privacy issues in RFID / Boyeon Song -- DoS attacks on RFID systems: privacy vs. performance / Dang Nguyen Duc, Kwangjo Kim -- Malware protection on RFID-enabled supply chain management systems in the EPCglobal Network / Qiang Yan, Yingjiu Li, Robert H. Deng -- Addressing covert channel attacks in RFID-enabled supply chains / Kirti Chawla, Gabriel Robins -- Building scalable, private RFID systems / Li Lu.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed March 19, 2013).
Keywords: Sensor networks -- Security measures; Radio frequency identification systems -- Security measures; IT policy and standardization; IT security and ethics; Mobile and wireless computing; Privacy requirements and solutions; RFID standardization and communication; Software and systems design; Electronic books